The diffusion of innovations to improve the French urban environment (1890s-1940). - Frioux, Stéphane (Deutsches Institut für Urbanistik, 2018)
The circulation of information and knowledge about sanitary engineering (water supply, sewage and solid waste disposal and treatment) from the late nineteenth century to World War II highlights a specific process of urban innovation diffusion. This process worked inside the French urban network without any strong hierarchical pattern but in a rather horizontal way, Paris being rather an exception than a replicable model. A transnational dimension appears clearly, especially in the pre-1914 period. lt underlines the ability of some local governments to implement technological facilities in a context of relatively weak state expertise and intervention. A careful study of several dozens of decision-making processes, from the documentation phase to the opening ceremonies of new facilities, enables the author to perceive the complex path through which modern technology penetrated cities.
Keywords: Stadtgeschichte; Stadtforschung; Technische Infrastruktur; Wasserversorgung; Kanalisation; Kommunalisierung; Transformation; Innovation; Diffusion; Stadthygiene